Inside Front Cover. Issue 9 (28th August 2018) - Zhang, P.; Du, HB.; Tong, GD.; Li, XK.; Sun, XH.; Chi, XL.; Xing, YF.; Zhou, ZH.; Li, Q.; Chen, B.; Wang, H.; Wang, L.; et al.
Abstract : The cover image, by P. Zhang et al., is based on the Original Article Serum hepatitis B surface antigen correlates with fibrosis and necroinflammation: A multicentre perspective in China, DOI:10.1111/jvh.12903 .